Peran Badan Usaha Milik Nagari Dalam Pembangunan Ekonomi Nagari Di Nagari Pakan Sinayan Kecamatan Banuhampu - Iqbal, Muhammad (Jurnal Teori dan Riset Administrasi Publik, 2025)
This study aims to analyze the role of the Village-Owned Enterprise (BUMNag) of Pakan Sinayan in the economic development of Pakan Sinayan Village, Banuhampu District, Agam Regency. BUMNag is an economic institution established to promote community empowerment and sustainable local resource management. In practice, BUMNag contributes through agricultural land management, home-based industry development, and entrepreneurship training programs for the community. These initiatives have proven effective in increasing income and creating employment opportunities within the village. However, BUMNag's operations face several challenges. Internally, limited human resources and weak managerial capacity pose significant constraints. Externally, low community participation and inadequate socialization by the village government have hindered optimal program implementation. Many community members still lack full understanding of the programs' benefits, resulting in low engagement levels. To address these issues, BUMNag has implemented strategic measures, including enhanced collaboration among village stakeholders, needs-based program development, and capacity-building through technical and managerial training. The study concludes that BUMNag's success largely depends on synergy between the village government, BUMNag management, and the community. With professional and participatory management, BUMNag has significant potential to accelerate inclusive and sustainable economic development in the village.